Exploring the Effects of Cancer as a Traumatic Event on Italian Adolescents and Young Adults: Investigating Psychological Well-Being, Identity Construction and Coping Strategies - Chiara Ionio; Francesca Bigoni; Maddalena Sacchi; Marco Zecca; Elena Bergami; Marta Landoni; Giulia Ciuffo; Anna Rovati; Damiano Rizzi (MDPI AG, 2023)
Cancer in adolescence is considered a family disease that can have numerous negative psychological consequences for adolescents and the entire household. The aim of this study was to investigate the impact of oncological disease in adolescence, with particular reference to the psychological and post-traumatic consequences for the adolescents themselves and the family system. An explorative case-control study was conducted with 31 adolescents (mean age 18.03 ± 2.799) hospitalised for cancer at IRCCS San Matteo Hospital in Pavia and 47 healthy adolescents (mean age 16.17 ± 2.099). The two samples completed a survey that included sociodemographic information and questionnaires assessing psychological well-being, traumatic effects of the disease, and adequacy of the relationship with parents. 56.7% of oncology adolescents scored below average in psychological well-being, and a small proportion of them fell within the range of clinical concern for anger (9.7%), PTS (12.9%), and dissociation (12.9%). Compared with peers, there were no significant differences. However, in contrast to peers, oncology adolescents showed a strong influence of the traumatic event on the construction of their identity and life perspectives. A significantly positive correlation also emerged between adolescents' psychological well-being and the relationship with their parents (mothers: r = 0.796; p < 0.01; fathers: r = 0.692; p < 0.01). Our findings highlight how cancer in adolescence could represent a central traumatic event that can shape the identity and life of teenagers who are in an intrinsically delicate and vulnerable stage of life.